Makey Makey - Ng, Sandy 1991- (Ann Arbor, Michigan Cherry Lake Publishing, 2017)
Makey Makey is a kit that helps you turn everyday objects into touchpads that control your computer's keyboard.
"21st Century skills innovation library."
Includes bibliographical references (page 31) and index.
Science Books and Films
5.0
4-7
Keywords: Microcontrollers -- Juvenile literature; Electronic circuits -- Juvenile literature; Inventions -- Juvenile literature